2013
DOI: 10.1186/1916-0216-42-61
|View full text |Cite
|
Sign up to set email alerts
|

Rates of thyroid malignancy by FNA diagnostic category

Abstract: BackgroundFine needle aspiration (FNA) of thyroid nodules is a cornerstone of surgical decision making in thyroid cancer. The most widely utilized system for reporting thyroid FNA results is the Bethesda System, which includes predicted malignancy rates for each FNA category. To date there have been few studies to determine whether these predictions are widely applicable.MethodsAll thyroid FNA results at the Queen Elizabeth II Health Science Centre from 2006–2010 were included in this study. The results were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 9 publications
9
41
2
Order By: Relevance
“…In accordance with the findings in this study, others have also found a high malignancy risk in pediatric BIV and BV nodules, 58 per cent and 100 per cent, respectively [10]. In comparison, adult BIV and BV lesions carry a malignancy risk of 20-36 per cent and 60-94 per cent, respectively [6,[11][12][13][14][15][16][17][18]. BVI nodules seem to be at almost 100 per cent risk of malignancy in children as well as in adults [11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with the findings in this study, others have also found a high malignancy risk in pediatric BIV and BV nodules, 58 per cent and 100 per cent, respectively [10]. In comparison, adult BIV and BV lesions carry a malignancy risk of 20-36 per cent and 60-94 per cent, respectively [6,[11][12][13][14][15][16][17][18]. BVI nodules seem to be at almost 100 per cent risk of malignancy in children as well as in adults [11][12][13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…In comparison, adult BIV and BV lesions carry a malignancy risk of 20-36 per cent and 60-94 per cent, respectively [6,[11][12][13][14][15][16][17][18]. BVI nodules seem to be at almost 100 per cent risk of malignancy in children as well as in adults [11][12][13][14][15][16][17][18]. Most agree that the appropriate management for BVI nodules N1 cm in size is total thyroidectomy although the benefit of prophylactic central lymph node dissection is under debate [7,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, like all grading systems it is subject to interobserver variability and there have been significant discrepancies in the literature concerning the risk of malignancy in individual diagnostic categories, particularly for those lesions classified as Bethesda 3 (atypia of undetermined significance/follicular lesion of undetermined significance) and Bethesda 4 (suspicious for a follicular neoplasm), summarised in Table 2. 3,[7][8][9][10][11][12][13][14] For example, the reported risk of malignancy in Bethesda 3 nodules has ranged from 6% to 50%. 8,10 Furthermore, many of the cohorts from which the risks of malignancy (and therefore the standardised treatment recommendations) were derived were retrospectively accrued series based on re-examination by subspecialist endocrine cytopathologists.…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11] Other large validation cohorts were from the databases of surgical units and subject to a significant referral bias towards patients considered at high clinical risk of malignancy and therefore surgical referral. 12,14 To our knowledge there have been no large series detailing the risk of malignancy for the individual Bethesda categories in the Australian population. As a result, the published risks of malignancy for the different Bethesda categories may not represent the actual risk encountered in community based Australian practice.…”
Section: Introductionmentioning
confidence: 99%